2003
DOI: 10.1023/b:bebm.0000017087.90585.a9
|View full text |Cite
|
Sign up to set email alerts
|

Glyprolines and Semax Prevent Stress-Induced Microcirculatory Disturbances in the Mesentery

Abstract: One-hour immobilization stress considerably disturbed microcirculation in the mesentery: blood flow in small mesenteric vessels decreased or stopped and numerous hemorrhages appeared. Lymphatic vessels lost spontaneous activity and did not respond to norepinephrine. Administration of Semax and glyprolines 1 h before stress decreased the severity of stress-induced microcirculatory disturbances. PGP and GP were most effective in this respect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…Vital microscopy of mesenteric microcirculatory bed was performed at various stages of peritonitis (30 min and 2, 6, and 18 h after administration of thioglycollate) [3].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vital microscopy of mesenteric microcirculatory bed was performed at various stages of peritonitis (30 min and 2, 6, and 18 h after administration of thioglycollate) [3].…”
Section: Methodsmentioning
confidence: 99%
“…Pretreatment with proline-containing peptides (PGP, PG, and GP) prevents the development of stress-induced microcirculatory disturbances [3,4].…”
mentioning
confidence: 99%
“…The function of these cells is characterized by a drastic increase in the level of secretory activity. We previously showed that injection of glyprolines before stress exposure significantly attenuated the stressogenic disorders in the rat mesenteric microcirculation [2]. Stabilization of mast cells by preinjection of ketotifene prevented stressinduced disorders in contractile activity of mesenteric lymph vessels and reduced stressogenic activation of mast cells [1].…”
Section: Resultsmentioning
confidence: 98%
“…We previously showed that injection of glyprolines before stress exposure significantly attenuated the stressogenic disorders in the rat mesenteric microcirculation [2]. Stabilization of mast cells by preinjection of ketotifene prevented stressinduced disorders in contractile activity of mesenteric lymph vessels and reduced stressogenic activation of mast cells [1]. Increased secretory activity of mast cells during inflammation suggested that the protective effect of PGP is mediated by inhibition of secretory activity of mast cells during inflammation-induced disorders of contractile activity of lymph vessels.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation